Sistem Pakar Diagnosa Stunting Pada Balita Menggunakan Metode Naive Bayes - Dea Sinta Nurhidayah (JATISI, 2026)
The problem of stunting among children in Indonesia has decreased in prevalence from 24.4% in 2021 to 21.6% in 2022. Therefore, the government really hopes that the prevalence of stunting will continue to decline in order to create healthy and stunting-free children. However, what is happening at Posyandu Wargo Rukun Dusun Dosaran, Klaten Regency is that there are still many parents' concerns about the prevalence of stunting in children, this has become a concern for parents. Due to the many factors of accessibility to health services and economic factors, many parents often diagnose themselves without adequate knowledge base and only wonder whether their child is stunted. To overcome this problem, this research aims to develop an "Expert System for Stunting Diagnosis in Toddlers Using the Naive Bayes Method" to help parents detect early symptoms of stunting in their children based on accurate and relevant information sources obtained from experts.